Incidence, risk factors and perinatal outcomes for placenta accreta in Australia and New Zealand: a case–control study. Issue 10 (5th October 2017) - Farquhar, Cynthia M; Li, Zhuoyang; Lensen, Sarah; McLintock, Claire; Pollock, Wendy; Peek, Michael J; Ellwood, David; Knight, Marian; Homer, Caroline SE; Vaughan, Geraldine; Wang, Alex; Sullivan, Elizabeth
Abstract : Objective: Estimate the incidence of placenta accreta and describe risk factors, clinical practice and perinatal outcomes. Design: Case–control study. Setting: Sites in Australia and New Zealand with at least 50 births per year. Participants: Cases were women giving birth (≥20 weeks or fetus ≥400 g) who were diagnosed with placenta accreta by antenatal imaging, at operation or by pathology specimens between 2010 and 2012. Controls were two births immediately prior to a case. A total of 295 cases were included and 570 controls. Methods: Data were collected using the Australasian Maternity Outcomes Surveillance System. Primary and secondary outcome measures: Incidence, risk factors (eg, prior caesarean section (CS), maternal age) and clinical outcomes of placenta accreta (eg CS, hysterectomy and death). Results: The incidence of placenta accreta was 44.2/100 000 women giving birth (95% CI 39.4 to 49.5); however, this may overestimated due to the case definition used. In primiparous women, an increased odds of placenta accreta was observed in older women (adjusted OR (AOR) women≥40 vs <30: 19.1, 95% CI 4.6 to 80.3) and current multiple birth (AOR: 6.1, 95% CI 1.1 to 34.1). In multiparous women, independent risk factors were prior CS (AOR ≥2 prior sections vs 0: 13.8, 95% CI 7.4 to 26.1) and current placenta praevia (AOR: 36.3, 95% CI 14.0 to 93.7). There were two maternal deaths (case fatality rate 0.7%). Women with placenta accreta were more likely to have a caesarean section (AOR: 4.6, 95% CI 2.7 to 7.6) to be admitted to the intensive care unit (ICU)/high dependency unit (AOR: 46.1, 95% CI 22.3 to 95.4) and to have a hysterectomy (AOR: 209.0, 95% CI 19.9 to 875.0). Babies born to women with placenta accreta were more likely to be preterm, be admitted to neonatal ICU and require resuscitation.